Kualitas mie basah dengan substitusi tepung sukun dan gel okra sebagai pengikat: The quality of wet noodles with breadfruit flour and okra gel substitution as a binder - Windyasari, Alexandra Paska Selma; Swasti, Yuliana Reni; Pranata, Franciscus Sinung (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Wet noodles are wheat-based food products molded lengthwise, boiled, and contain up to 52% water. Market-available wet noodles often lack nutrients, prompting research to address this issue. This study utilizes breadfruit flour as a wheat substitute and okra gel as a binding agent. The aim is to assess wet noodles' chemical, physical, microbiological, and organoleptic qualities using breadfruit flour and okra gel and determine the optimal concentration for the best quality. The research aims to produce wet noodles with improved nutritional content, particularly high fiber levels, and reduce wheat flour usage. A completely randomized design with four treatment levels of breadfruit flour and okra gel ratios 0:0 (K), 10:10 (B), 20:20 (B), and 30:30 (C) was employed. The study analyzed wet noodle quality based on chemical, physical, microbiological, and organoleptic parameters. Results indicate that wet noodles have water content ranging from 31.33% to 47.6%, ash content ranging from 1.03% to 2.7%, protein content ranging from 7.54% to 10.19%, insoluble fiber content ranging from 7.7% to 9.03%, soluble fiber content ranging from 5.5% to 6.3%, cooking loss ranging from 6.50% to 7.71% and tensile strength ranging from 0.013% to 0.019%. Total plate count and yeast mold count meet the quality standards specified in SNI 2987-2015. The best quality wet noodles were observed in the 30:30 (C) treatment.